Intrauterine insemination or in vitro fertilization in male infertility? - Manzur, Alejandro (2014)
Arguments for and against intrauterine insemination versus in vitro fertilization/ICSI in cases of infertile couples with male factor are discussed. Several variables influencing the results must be considered prior to indicatingthe technique, including cost-benefit and proportionality of the therapy.